Grenada. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Granada during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as leadership, communication, finance, trade, strategic plans, project management, organic agriculture, farm exploitation. , conflict resolution, inclusion of women and youth, disease control and nutmeg production.